Self-assessment of independence in older people: First results from an open-access website for senior citizens and caregivers in France. Issue 2 (May 2018) - Koskas, Pierre; Wolfowicz, B
Background: E-health initiatives on the Internet can be used to provide support to people with chronic diseases and to their caregivers. In 2014/2015, we created a free website called jesuisautonome.fr where older people, or their carers on their behalf, can assess their independence in daily living by filling out a simple questionnaire. Objectives: To evaluate the interest of the public in websites of this kind, by analysing home care plans obtained via the self-assessment questionnaire. We also describe patterns of use and visitor behaviour. Method: Over a period of 6 months, we analysed data from the website in terms of the basic characteristics of the user; the number of questionnaires completed; the main types of needs in terms of home support; and data from Google Analytics about the number of visitors, user behaviour and behaviour flow. Results: During the 6-month study period, 439 visitors to the site either viewed, part-completed or fully completed the questionnaire. A total of 190 users completed the questionnaire. Seventy-one per cent of the completed questionnaires were from family caregivers, and 29% were from senior citizens. The mean age of those receiving care was 78 ± 10.46 years. Their main needs were for domiciliary care (29.3%). Data from Google Analytics showed about 420 visits per month. Approximately 7.5% completed a questionnaire, approximately 5.3% downloaded a home care plan and there was a bounce rate of about 62%. Conclusion: First results from this website tend to endorse its use as a means of making practical solutions available to caregivers and older people.